The effect of specialized Hongquan martial arts training on the development of visual-motor integration in children - Zhang, Juan-Juan; Lu, Jia; Liu, Chen-Tao (Frontiers in Psychology, 2025)
ObjectiveThis study examines the effects of different durations of Hongquan martial arts training on the development characteristics of visual-motor integration (VMI) abilities in children and the relevant influencing factors.MethodsA total of 59 children, aged 9–11 years, who were active practitioners of Hongquan martial arts were recruited from the Lu Jia Hongquan Cultural Heritage Base and the Xiaolong Martial Arts School in Xi’an. Additionally, 21 children of the same age were recruited from a Primary School in Hi-Tech District, Xi’an, as the normal control group. The subjects were divided into four groups based on their years of training: the no-training group, 1-year training group, 3 years training group, and 5+ years training group. The visual-motor integration ability, visual perception ability, action coordination ability, attention, and executive function of the subjects were tested using the Beery-Buktenica developmental test of visual-motor integration (VMI-6), Test of Visual Perception Skills 4th edition (TVPS-4), Motor coordination evaluation index system, Children Attention Test, Flanker task, more-odd shifting task, and 1-back task, respectively.ResultsCompared to the no-training group, the one-year Hongquan martial arts practitioners showed significant improvement in working memory updating function (p < 0.05), and the three-year Hongquan martial arts practitioners showed significant improvement in balance ability (p < 0.01); those with five or more years of Hongquan martial arts training showed significant improvements in their VMI abilities (p < 0.01), particularly in visual perception (p < 0.05), spatial relationships (p < 0.01), overall coordination (p < 0.05), balance ability (p < 0.01), attention breadth (p < 0.01), and inhibitory control (p < 0.05). In addition, the 5 + years of training group showed significantly higher levels of balance ability and overall coordination ability than the group with 1 year of Hongquan martial arts training (p < 0.05), and better overall coordination ability and attention allocation than the group with 3 years of Hongquan martial arts training (p < 0.05). However, the working memory updating function of the 3-years and 5+ years groups was significantly lower compared to the 1-year group (p < 0.05).ConclusionLong-term Hongquan martial arts training for more than 5 years during the sensitive period for the development of VMI abilities can effectively enhance the visual-motor integration abilities of children.